Avaliação do Desenho da Ferramenta de Monitoramento das Ações e Projetos Prioritários – MAPP no Governo do Estado do Ceará - Rego, Joizia Lima Cavalcante (2015)
The objective of this dissertation is to evaluate the design of the Management and Planning tool adopted by the state of Ceará, denominated Monitoring of Actions and Priority Projects - MAPP. The motivation for the investigation part of a restlessness occupational, to understand the concepts and execution, as well as instigating reflections and discussions about public spending control instrument adopted by the Government of the State of Ceará. The time frame was the 2007 to 2014 period of implementation of the Management and Planning tool MAPP. This evaluation seeks to discover through qualitative analysis from the perspective of some analytical axes of the in-depth evaluation (RODRIGUES, 2008; 2011) which considers the conceptual bases, the institutional trajectory and analysis of context. In this ambit, the methodological perspective uses the bibliographic research technique, documentary and open interviews, which provided clues for understanding the perceptions of those involved subjects, the creators and performers tool as well as examine the socio-political context. To understand the MAPP design context in the state, promotes the theoretical dialogue between the positivist conception of the Holanda (2006), the constructivist paradigm of the authors Guba and Lincoln (2011), and the Lejano post-constructivist (2012) in that supports new reflections on the conduct and monitoring of social projects of government from the perspective of democratic participation of the subjects involved.